Animal models for antidepressant activity assay on natural and conventional agents: A review of preclinical testing - Ani Kristiyani; Zullies Ikawati; Andayana Puspitasari Gani; Zaenal Muttaqien Sofro (Shahrekord University of Medical Sciences, 2024)
Depression is characterized by symptoms such as insomnia, change in appetite and body weight, impaired concentration, lethargy, agitation, psychomotor retardation, anhedonia, feelings of worthlessness, and suicidal thoughts. Various methods have been applied to assess the efficacy of antidepressants and associated molecular processes. However, guidance on the selection of methods for antidepressant testing is still lacking. This article provides a comprehensive review focusing on animal models of depression and the behavioral and molecular changes. A literature search was conducted on platforms, such as PubMed, Google Scholar, Scopus, and Science Direct to find relevant articles. This review found that chronic unpredictable mild stress might be the best and most commonly used model for inducing depression and simulating human depressive states in animals. This model employs a naturalistic approach to expose animals to unpredictable stressors that disrupt homeostasis and cause somatic, physiological, neurobiological, and biochemical disorders and behaviors. The forced swim test (FST) is the most frequently used simple behavioral testing method that is consistent with antidepressant effects, reduces immobility time, and serves as the leading indicator of antidepressant effectiveness. The most commonly observed molecular changes are those related to the levels of monoamine neurotransmitters, such as 5-hydroxytryptamine, dopamine, norepinephrine, and brain-derived neurotrophic factor (BDNF), which are the main etiological contributors to depression. The findings from this review will contribute to ongoing efforts to discover and develop drug candidates for the treatment of depression.